2011
DOI: 10.1111/j.1476-5381.2011.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aldehyde dehydrogenase 2 expression in rat blood vessels during glyceryl trinitrate tolerance development and reversal

Abstract: BACKGROUND AND PURPOSERecent studies have suggested an essential role for aldehyde dehydrogenase 2 (ALDH2) in the bioactivation of organic nitrates such as glyceryl trinitrate (GTN). In the present study, we utilized an in vivo GTN tolerance model to further investigate the role of ALDH2 in GTN bioactivation and tolerance. EXPERIMENTAL APPROACHWe assessed changes in aortic ALDH activity, and in ALDH2 protein expression in various rat blood vessels (aorta, vena cava, femoral artery and femoral vein) during cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…We evaluated Quest MRI during sustained superoxide production from the xanthine/xanthine oxidase reaction (23, 24). We provide proof-of-concept data that Quest MRI can be applied to evaluate hippocampus subfields in vivo in 3 disease models: aldehyde dehydrogenase 2-knockout mice, 5xFAD mice, and UBE3A-knockout mice (25)(26)(27)(28)(29). Aldehyde dehydrogenase 2 mice are also called HNE mice because they exhibit a greater-than-normal hippocampus concentration of the peroxidation product HNE (the earliest evidence for oxidative stress in patients with prodromal AD (30), together with spatial learning and memory impairments and age-dependent spontaneous AD-like histopathology (17).…”
mentioning
confidence: 99%
“…We evaluated Quest MRI during sustained superoxide production from the xanthine/xanthine oxidase reaction (23, 24). We provide proof-of-concept data that Quest MRI can be applied to evaluate hippocampus subfields in vivo in 3 disease models: aldehyde dehydrogenase 2-knockout mice, 5xFAD mice, and UBE3A-knockout mice (25)(26)(27)(28)(29). Aldehyde dehydrogenase 2 mice are also called HNE mice because they exhibit a greater-than-normal hippocampus concentration of the peroxidation product HNE (the earliest evidence for oxidative stress in patients with prodromal AD (30), together with spatial learning and memory impairments and age-dependent spontaneous AD-like histopathology (17).…”
mentioning
confidence: 99%
“…This value agrees well with most published data including results obtained with human arterial and venous blood vessels (Hink et al ., 2007; Szöcs et al ., 2007; Wenzel et al ., 2007). However, one study found that ALDH2 expression was markedly reduced to 20% of controls in vena cava of nitrate-tolerant rats (D'Souza et al ., 2011). …”
Section: Resultsmentioning
confidence: 99%
“…Despite general agreement on the essential role of ALDH2 inactivation in nitrate tolerance, this concept has been questioned in a recent study showing that the haemodynamic response recovered more rapidly after GTN treatment than total vascular ALDH activity (D'Souza et al ., 2011). Although GTN bioactivation is catalysed by cytosolic rather than mitochondrial ALDH2 (Beretta et al ., 2012), exposure of blood vessels to the nitrate appears to result in mitochondrial oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, ALDH2 knockout in mice or the presence of loss-offunction mutations of ALDH2 in humans (for example in Chinese/Japanese), are associated with attenuation of nitroglycerin effect [29]. On the other hand, D'Souza et al [30] have recently presented compelling data dissociating the time course of ALDH2 inhibition by nitroglycerin from that of tolerance induction, and therefore suggesting that ALDH2 is certainly not the sole, or even predominant, mechanism of tolerance induction.…”
Section: Smooth Muscle Cellmentioning
confidence: 95%